Beyond O&P Times Three. (June 2018) - Mohapatra, Sonmoon; Singh, Dhruv Pratap; Alcid, David; Pitchumoni, Capecomorin S
Abstract : N/A: Although examination of the stool for ova and parasites times three (O&P ×3) is routinely performed in the United States (US) for the evaluation of persistent and/or chronic diarrhea, the result is almost always negative. This has contributed to the perception that parasitic diseases are nearly non‐existent in the country unless there is a history of travel to an endemic area. The increasing number of immigrants from third‐world countries, tourists, and students who present with symptoms of parasitic diseases are often misdiagnosed as having irritable bowel syndrome or inflammatory bowel disease. The consequences of such misdiagnosis need no explanation. However, certain parasitic diseases are endemic to the US and other developed nations and affect both immunocompetent and immunocompromised patients. Testing for parasitic diseases either with O&P or with other diagnostic tests, followed by the recommended treatment, is quite rewarding when appropriate. Most parasitic diseases are easily treatable and should not be confused with other chronic gastrointestinal (GI) disorders. In this review, we critically evaluate the symptomatology of luminal parasitic diseases, their differential diagnoses, appropriate diagnostic tests, and management.